Central nervous system hemorrhage in thrombocytopenic patients: computed tomographic findings in 21 cases Hemorragia do sistema nervoso central em pacientes trombocitopênicos: achados por tomografia computadorizada em 21 casos - Emerson L. Gasparetto; Paulo R. Benites Filho; Taísa Davaus; Arnolfo de Carvalho Neto (Arquivos de Neuro-Psiquiatria)
OBJETIVE: To describe the CT scan findings of 21 thrombocytopenic patients with central nervous system (CNS) hemorrhage. METHOD: Retrospective study of the computed tomography (CT) of 21 platelet-depleted patients with CNS hemorrhage. One patient presented two episodes of hemorrhagic episode with different intervals. The clinical data were obtained by the review of the medical records. Two radiologists analyzed the films and reached the decisions by consensus. The following findings were studied: type of bleeding, number of lesions, topography, laterality, size and associated findings. RESULTS: Intraparenchymal hemorrhage (IPH) was the most common findings, found in 20 cases, being six of them associated with subarachnoid and intraventricular hemorrhages. The size of the lesions varied between 1.8 and 10.5 cm. The parietal lobes were more commonly affected (n=11, 50%), followed by the temporal (n=7, 31.8%), frontal (n=7, 31.8%) and occipital (n=2, 9.09%) lobes. In 15 cases (68.2%) there was a single area of hemorrhage and in the remaining cases there were multiple hemorrhages. Associated findings were found in 20 cases. The most prevalent were edema (n=17, 77.3%), hydrocephalus (10, 45.4%) and midline shift (n=9, 41%). CONCLUSION: The most frequent CT scan findings in thrombocytopenic patients with CNS hemorrhage are single IPH, located mostly in the parietal, temporal and frontal lobes, with varied sizes and associated with edema, hydrocephalus and midline shift. OBJETIVO: Descrever os achados tomográficos de 21 pacientes trombocitopênicos com hemorragia no sistema nervoso central (SNC). MÉTODO: Estudo retrospectivo das tomografias computadorizadas (TC) de 21 pacientes trombocitopênicos que apresentaram hemorragia no SNC. Um dos pacientes apresentou 2 episódios hemorrágicos em épocas diferentes. Os dados clínicos foram obtidos por revisão de prontuários médicos. Dois radiologistas analisaram os exames e estabeleceram os achados por consenso. Os seguintes achados foram estudados: tipo de sangramento, número de lesões, topografia, lateralidade, tamanho e achados associados. RESULTADOS: A hemorragia intraparenquimatosa foi o achado mais comum, observada em 20 casos, sendo que em seis deles apresentavam hemorragia subaracnóidea e intraventricular associadas. O tamanho das lesões variou entre 1,8 e 10,5 cm (mediana= 4,5 cm). Os lobos parietais foram mais acometidos (n=11, 50%), seguidos pelos temporais (n=7, 31,8%), frontais (n=7, 31,8%) e occipitais (n=2, 9,09%). Em 15 casos (68,2%) houve uma única área de hemorragia, e nos demais múltiplas áreas foram observadas. Em 20 casos foram encontrados achados associados, sendo mais comum edema (n=17, 77,3%), hidrocefalia (n=10, 45,4%) e desvio da linha média (n=9, 41%). CONCLUSÃO: Os achados tomográficos mais freqüentes em pacientes trombocitopênicos com hemorragia cerebral são lesões intraparenquimatosas únicas acometendo principalmente os lobos parietais, temporais e frontais, com tamanhos variados e associadas a edema, hidrocefalia e desvio da linha média.